Cultura de información, política y mundos posibles - Jesús Galindo Cáceres (Estudios sobre las Culturas Contemporáneas)
A reflection on contemporary globalization of information culture. There is talk of a transition from an information society to a community of communicatioa On the basis of the concept of a society of disinformation, a new perspective is offered on the forms in which contemporary societies are being configured. At the same time the author attempts to sketch, from an historical perspective, some of the possible social configurations of the future.